GE_GERICHTE A/1759/2006 vom 29. August 2006 - GE Cour de justice (2006)
; CHÔMAGE ; AC ; PRESTATION D'ASSURANCE(AC) ; PRESTATION EN ARGENT; RESTITUTION(EN GÉNÉRAL) ; PÉREMPTION ; PRESTATION D'ASSURANCE(EN GÉNÉRAL) ; INDU | LPGA25